Gimme some sugar - Harper, Molly (Southern eclectic, 2019)
A young widow returns to Lake Sackett, Georgia to face the ghosts of her past--and decide if she's ready to take another chance on love--in the third sparkling Southern Eclectic novel that "goes down as easy as honey on a deep-fried Twinkie" (Library Journal, on Sweet Tea and Sympathy).